Fused deposition fabrication of high-quality zirconia ceramics using granular feedstock. Issue 24 (15th December 2021) - Shen, Ting; Xiong, Huiwen; Li, Zhiyou; Zhang, Lei; Zhou, Kechao
Abstract: Benefiting from the mature technology of ceramic injection molding, Fused deposition modeling based on highly-filled ceramic-polymer granular feedstocks has been showing great potential and advantage for fabricating 3D ceramics. Herein, 3D zirconia ceramics using granular feedstock were fabricated, and typical morphology, surface quality, and effect of the thermal accumulation on 3D structure were clarified. Typical morphology of printing steps on the surface were quantitatively characterized, and determined by the surface curvature and layer height of the printed structure. Aligned triangular pores were confirmed at the junction of the deposited filaments with elliptical cross-section morphology. Simple square plates with different size were used to illustrate the influence of thermal accumulation on the morphology of 3D structure. Small printing size increased the thermal accumulation during deposition, resulting in decreased printing quality caused by the secondary over-melting of former deposited layers. Except for the pores at the junctions, dense zirconia ceramics with uniform structure and smooth surface could be achieved. A low-cost and high-quality route for the preparation of 3D ceramics was demonstrated via FDM of highly-filled granular feedstocks.